2014
DOI: 10.7589/2013-05-109
|View full text |Cite
|
Sign up to set email alerts
|

HEALTH EVALUATION AND SURVEY OF ZOONOTIC PATHOGENS IN FREE-RANGING CAPYBARAS (HYDROCHOERUS HYDROCHAERIS)

Abstract: ABSTRACT:Capybaras (Hydrochoerus hydrochaeris) are the world's largest rodents and play an epidemiologic role in the transmission of zoonotic pathogens, including the causative agents of Brazilian spotted fever, leptospirosis, and others. We surveyed the health of 31 free-ranging capybaras at the Alberto Lö fgren State Park, São Paulo, Brazil using a variety of diagnostic methods. Hematology and serum chemistry were consistent with mild malnutrition and parasitism but did not indicate severe physiologic imbala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 16 publications
0
28
1
Order By: Relevance
“…However, in the present study, all the animals were found to be unreactive to all 28 serovars, using MAT. These unexpected findings may be attributed to low environmental contamination in both free-ranging and captive settings, since rodents have been considered the reservoirs responsible for leptospirosis transmission 2 . Nonetheless, wild species in urban areas and in captivity should be always screened as potential reservoirs of environmental contamination, and further studies should be conducted to fully establish the role of each of these species in the disease cycle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study, all the animals were found to be unreactive to all 28 serovars, using MAT. These unexpected findings may be attributed to low environmental contamination in both free-ranging and captive settings, since rodents have been considered the reservoirs responsible for leptospirosis transmission 2 . Nonetheless, wild species in urban areas and in captivity should be always screened as potential reservoirs of environmental contamination, and further studies should be conducted to fully establish the role of each of these species in the disease cycle.…”
mentioning
confidence: 99%
“…and Toxoplasma gondii 1,2 . Capybaras (Hydrochoerus hydrochaeris), collared peccaries (Pecari tajacu), and white-lipped peccaries (Tayassu pecari) are very valuable, for their meat and leather, when commercially raised, in both national and international markets 2 . Furthermore, these animals may play an important role in zoonotic pathogen cycles by serving as sentinels with active surveillance in both captive and free-ranging populations.…”
mentioning
confidence: 99%
“…In contrast, Chiacchio et al (2014) also studied the Campinas region, but did not find any reactive samples in their research. The high prevalence detected in this study may be explained by data reported by Ribeiro et al (2013) that points to higher rates of spotted fever in the most densely occupied regions of each state.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the presence of antibodies against Toxoplasma gondii, Neospora caninum, Leptospira spp., Trypanosoma cruzi, and Sarcocystis neurona in capybaras in the state of São Paulo, Brazil (VALADAS et al, 2010;CHIACCHIO et al, 2014), emphasizing the importance of this species as a potential transmitter of infectious parasitic diseases to humans and other animals.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring these animals in urban areas is important since they can transmit several zoonoses. Their role in transmission of Rickettsia rickettsii is well established, but capybaras can also play a role in the transmission of Leishmania spp., Leptospira spp., Trypanosoma spp., Enterobacteriaceae (including Salmonella enterica), Toxoplasma gondii and ectoparasites (Chiacchio et al, 2014).…”
mentioning
confidence: 99%